👤

14 + { −7 + [ 4 − 11 + ( 5 − 4) − (−6 + 8 − 3 )] + 7}=?

Răspuns :

Răspuns: [tex]\color{red}\Large\boxed{ \bf 9}[/tex]

Explicație pas cu pas:

[tex]\large \bf 14 + \{ -7 + [ 4 - 11 + ( 5 - 4) -(-6 + 8 - 3 )] + 7\}=[/tex]

[tex]\large \bf 14 + \{ -7 + [ 4 - 11 + 1 -(2 - 3 )] + 7\}=[/tex]

[tex]\large \bf 14 + \{ -7 + [ 4 - 11 + 1 -(-1 )] + 7\}=[/tex]

[tex]\large \bf 14 + [ -7 + (4 - 11 + 1 +1 ) + 7]=[/tex]

[tex]\large \bf 14 + [ -7 + (-5) + 7]=[/tex]

[tex]\large \bf 14 + (-7 -5 + 7)=[/tex]

[tex]\large \bf 14 + (-12 + 7)=[/tex]

[tex]\large \bf 14 + (-5)=[/tex]

[tex]\large \bf 14 -5=[/tex]

[tex]\color{red}\Large\boxed{ \bf 9}[/tex]

==pav38==

Vezi imaginea Pav38